클록 송신 장치 및 방법, 클록 수신 장치 및 방법 - XU BOXIONG; GUAN TONGTONG; ZENG FUQIAN (2022)
클록 송신 장치 및 방법, 클록 수신 장치 및 방법에 있어서, 클록 송신 장치는 제1 입력 클록과 제2 입력 클록을 입력하도록 구성된 입력 유닛(102); 제1 샘플링 클록과 제2 샘플링 클록을 획득하고, 제1 샘플링 클록과 제2 샘플링 클록을 기반으로 제1 주파수 제어 워드를 결정하도록 구성된 샘플링 유닛(104) - 여기에서 제1 주파수 제어 워드는 제1 샘플링 클록과 제2 샘플링 클록 사이의 관계를 나타내는 데 사용되고, 제1 샘플링 클록은 제1 입력 클록에서 소정 규칙에 따라 결정하고, 제2 샘플링 클록은 제2 입력 클록에서 소정 규칙에 따라 결정함 - ; 및 제1 입력 클록을 기반으로 클록 신호를 생성하고, 클록 신호를 수신측에 송신하도록 구성된 송신 유닛(106) - 여기에서 클록 신호에서 적어도 제1 주파수 제어 워드가 전달됨 - 을 포함한다. A clock sending apparatus and method, and a clock receiving apparatus and method. The clock sending apparatus comprises: an input unit (102), configured to input a first input clock and a second input clock; a sampling unit (104), configured to acquire a first sampling clock and a second sampling clock, and determine a first frequency control word according to the first sampling clock and the second sampling clock, wherein the first frequency control word is used for indicating the relationship between the first sampling clock and the second sampling clock, the first sampling clock is determined by the first input clock according to a preset rule, and the second sampling clock is determined by the second input clock according to the preset rule; and a sending unit (106), configured to generate a clock signal according to the first input clock, and send the clock signal to a receiving side, wherein the clock signal at least carries the first frequency control word.